A 10-year Australian experience of rare intraabdominal venous thrombosis with comparison to deep vein thrombosis and pulmonary embolism. Issue 3 (20th April 2023) - Oktaviana, Jesica; Lui, Brandon; Ho, Prahlad; Lim, Hui Y.
Abstract : Objective: Intra-abdominal venous thromboembolism is rare with heterogeneous management. We aim to evaluate these thrombosis and compare them to deep vein thrombosis and/or pulmonary embolism. Method: A 10-year retrospective evaluation of consecutive venous thromboembolism presentations (January 2011–December 2020) at Northern Health, Australia, was conducted. A subanalysis of intraabdominal venous thrombosis involving splanchnic, renal and ovarian veins was performed. Results: There were 3343 episodes including 113 cases of intraabdominal venous thrombosis (3.4%) – 99 splanchnic vein thrombosis, 10 renal vein thrombosis and 4 ovarian vein thrombosis. Of the splanchnic vein thrombosis presentations, 34 patients (35 cases) had known cirrhosis. Patients with cirrhosis were numerically less likely to be anticoagulated compared to noncirrhotic patients (21/35 vs. 47/64, P = 0.17). Noncirrhotic patients ( n = 64) were more likely to have malignancy compared to those with deep vein thrombosis and/or pulmonary embolism (24/64 vs. 543/3230, P < 0.001), including 10 patients diagnosed at time of splanchnic vein thrombosis presentation. Cirrhotic patients reported more recurrent thrombosis/clot progression (6/34) compared to noncirrhotic patients (3/64) (15.6 vs. 2.3 events/100-person-years; hazard ratio 4.7 (95% confidence interval 1.2–18.9), P = 0.030) and other venous thromboembolism patients (2.6/100-person-years; hazard ratio 4.7, 95% confidence interval 2.1–10.7; P < 0.001) with comparable major bleeding rates. All renal vein thrombosis were provoked including five malignant-related cases while three ovarian vein thrombosis occurred postpartum. No recurrent thrombotic or bleeding complications were reported in renal vein thrombosis and ovarian vein thrombosis. Conclusion: These rare intraabdominal venous thromboses are often provoked. Splanchnic vein thrombosis (SVT) patients with cirrhosis have a higher rate of thrombotic complications, while SVT without cirrhosis was associated with more malignancy. Given the concurrent comorbidities, careful assessment and individualized anticoagulation decision is needed.